2022
DOI: 10.1108/ebhrm-07-2022-0160
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital and employee job attitudes: the critical significance of work-life balance

Abstract: PurposeThe major goal of this research is to examine the work-life balance as a mediating factor in the association between psychological capital and employee attitudes including job satisfaction, organizational commitment and turnover intentions.Design/methodology/approachThe authors gathered data from prestigious healthcare institutes in North Indian states to test the suggested study model. Data were gathered from 613 personnel employed in public and private healthcare organizations via an online Google for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 101 publications
0
0
0
Order By: Relevance
“…Another result of the study demonstrates that women employed in the bank and working from home with high professional self-efficacy beliefs can achieve a work-life balance. Few studies in the literature (Badri, & Panatik, 2020) support this result (Siu, 2013;Polatçı & Akdoğan, 2014;Nina & Fauziah, 2017;Kaplan, 2018;Badri & Panatik, 2020;Akkuş, Najimudinova & Gül, 2020;Parray, Shah & Islam, 2022).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Another result of the study demonstrates that women employed in the bank and working from home with high professional self-efficacy beliefs can achieve a work-life balance. Few studies in the literature (Badri, & Panatik, 2020) support this result (Siu, 2013;Polatçı & Akdoğan, 2014;Nina & Fauziah, 2017;Kaplan, 2018;Badri & Panatik, 2020;Akkuş, Najimudinova & Gül, 2020;Parray, Shah & Islam, 2022).…”
Section: Discussionmentioning
confidence: 90%
“…Empirical studies have supported that individuals increase both the quality of work and the quality of life with their high self-efficacy belief (Nguyen & Nguyen, 2012;Nafei, 2015). Researchers emphasize that individuals with high self-efficacy beliefs are successful in establishing a work-life balance (Siu, 2013;Polatçı & Akdoğan, 2014;Nina & Fauziah, 2017;Kaplan, 2018;Badri & Panatik, 2020;Akkuş, Najimudinova & Gül, 2020;Parray, Shah & Islam, 2022). Moreover, empirical studies have also confirmed that self-efficacy reduces work and family conflict (Taşdelen-Karçkay, Bakalım & Yörük, 2016).…”
Section: Self-efficacy Belief and Work-life Balancementioning
confidence: 99%
See 1 more Smart Citation